设函数[img=66x25]1802cf04dfb2e71.png[/img]为方程[img=178x39]1802cf04edaac26.png[/img]所确定的隐函数,则[img=23x44]1802cf04f6c4d14.png[/img]等于
A: [img=42x45]1802cf04ff9821e.png[/img]
B: [img=42x45]1802cf0508098f3.png[/img]
C: [img=42x45]1802cf0510ca99e.png[/img]
D: [img=42x45]1802cf051a519e6.png[/img]
A: [img=42x45]1802cf04ff9821e.png[/img]
B: [img=42x45]1802cf0508098f3.png[/img]
C: [img=42x45]1802cf0510ca99e.png[/img]
D: [img=42x45]1802cf051a519e6.png[/img]
举一反三
- 设函数[img=66x25]18030312f19d88a.png[/img]为方程[img=178x39]18030312fe480cd.png[/img]所确定的隐函数,则[img=23x44]180303130625cd6.png[/img]等于 A: [img=42x45]180303130e7acd3.png[/img] B: [img=42x45]180303131768a20.png[/img] C: [img=42x45]180303131f0a78a.png[/img] D: [img=42x45]18030313276d33f.png[/img]
- 设函数[img=66x25]180386cbb083ee7.png[/img]为方程[img=178x39]180386cbbec27d5.png[/img]所确定的隐函数,则[img=23x44]180386cbc701f09.png[/img]等于 A: [img=42x45]180386cbcf8da22.png[/img] B: [img=42x45]180386cbd8ed818.png[/img] C: [img=42x45]180386cbe1b2786.png[/img] D: [img=42x45]180386cbea80a6a.png[/img]
- 设函数[img=66x25]180383521cb12f2.png[/img]为方程[img=178x39]18038352250a93e.png[/img]所确定的隐函数,则[img=23x44]180383522d02742.png[/img]等于 A: [img=42x45]1803835235c0248.png[/img] B: [img=42x45]180383523e91db3.png[/img] C: [img=42x45]180383524606a31.png[/img] D: [img=42x45]180383524eccffb.png[/img]
- 已知F(x)是f(x)的一个原函数,则[img=79x37]17e0a9ce46a20da.jpg[/img]? A: f(x)+C B: F(x)+C C: F(x)-f(x) D: CF(x)
- CF(H,E)在[-1,1]上取值,CF(H,E)[img=11x13]17e435cd2137a1f.jpg[/img]0表示( );CF(H,E)[img=11x13]17e43aa2c02c2f8.jpg[/img]0表示( );CF(H,E)=0表示( );CF(H,E)=-1表示( );CF(H,E)=1表示( )。